دراسة العلاقة بين التفكير النقدي والتعلم الذاتي المنظم: وجهات نظر بعض أساتذة الجامعات الليبية - Waragh, Imad Maoloud Salem (مجلة الاصالة, 2025)
The integration of critical thinking skills into English language curricula is vital for enhancing students’ ability to analyze, evaluate, and synthesize information effectively in both academic and real-world contexts. This paper investigates the relationship between critical thinking and selfregulated learning within English language teaching at higher education institutions in Libya. It is noted that a large number of university students are not aware or able to use their critical thinking skills in classroom .Therefore, Libyan students miss the opportunity to become selfregulated learners in terms of problem-solving, reflection, and discussion. Through qualitative research involving semi-structured interviews with 12 university lecturers, the paper examines the challenges educators face when integrating these skills, such as training programs and time constraints. The findings reveal that lecturers highly value the inclusion of critical thinking in their teaching recognizing its potential to promote deeper learning, enhance communication skills, and prepare students for the complexities of an interconnected and information-rich world. Finally, the integration of critical thinking into English language curricula not only strengthens language proficiency but also equips students with the analytical tools necessary for lifelong learning and informed decision-making.